2003
DOI: 10.1007/s00439-003-0988-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular variation at the apolipoprotein�B gene locus in relation to lipids and cardiovascular disease: a systematic meta-analysis

Abstract: Apolipoprotein B (apoB) is the sole protein component of low-density lipoprotein (LDL) and is thought to play an important role in atherogenesis. We performed a meta-analysis of the associations between the three most frequently investigated polymorphisms (XbaI, signal peptide insertion/deletion, EcoRI) in the apolipoprotein B (APOB) gene, lipid parameters, and the risk of ischemic heart disease (IHD). We restricted our analysis to Caucasians. Homozygotes for the XbaI X+ allele had significantly elevated level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
31
1
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 48 publications
9
31
1
1
Order By: Relevance
“…Our results in this population of obese subjects on spontaneous diet show an increase of the concentration of the LDL-cholesterol with the Del allele, which is in good agreement with most of the studies [7][8][9][10][11][12][13][14][15] but not all. [21][22][23] Nevertheless, the discrepancies between studies could be due to a different selection of subjects, in particular concerning the BMI, since in the latter studies, [21][22][23] subjects are described as 'healthy' or 'normal'.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results in this population of obese subjects on spontaneous diet show an increase of the concentration of the LDL-cholesterol with the Del allele, which is in good agreement with most of the studies [7][8][9][10][11][12][13][14][15] but not all. [21][22][23] Nevertheless, the discrepancies between studies could be due to a different selection of subjects, in particular concerning the BMI, since in the latter studies, [21][22][23] subjects are described as 'healthy' or 'normal'.…”
Section: Discussionsupporting
confidence: 92%
“…[7][8][9][10][11][12][13][14] A recent meta-analysis has shown that subjects with the Del/Del apoB genotype had higher cholesterol levels and an increased risk of coronary heart disease. 15 Improvements in the metabolic status of overweight patients can be achieved by even moderate weight loss: in particular, favorable changes in lipid profiles are observed. Genetic factors could also be involved in the variability of these changes.…”
Section: Introductionmentioning
confidence: 99%
“…Four SNPs at APOB were significantly related to lipids in our population: promoter SNP rs934197, non-synonymous SNPs rs1367117, rs1042031 and rs1801702. The most significant SNP rs1367117 is 2875 bp away from the extensively studied Ins/Del polymorphism [3]; therefore, it might tag the effect of the functional Ins/Del polymorphism. For SNP rs1042031 (aka EcoRI), the mean differences between the rare and common homozygous genotypes in our study (12.65 mg/dL) were similar to a meta-analysis that included 33 publications (15.46 mg/dL) [3], suggesting that the APOB gene exerted a comparable effect across ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
“…An SNP with the minor allele frequency (MAF) >0.05 and submitted to the dbSNP database by more than one source were mandatory requirements. Candidate SNPs that are most likely to be biologically relevant were selected using the following criteria: (1) non-synonymous SNPs, (2) had been examined in previous genetic studies, (3) with known functional relevance, or (4) located at evolutionarily conserved sequence homology (Vista website,http://genome.lbl.gov/vista/index.shtml). We also selected tagging SNPs across different human populations from the SeattleSNPs website (http://pga.gs.washington.edu/genes_genotyped.html).…”
Section: Snps Selection Criteria and Genotypingmentioning
confidence: 99%
See 1 more Smart Citation